Cherries botany, production and uses - Quero-García, J. (José); Iezzoni, Amy; Puławska, J. (Joanna); Lang, Gregory A. (CABI, 2017)
This book contains 20 chapters and is divided into 4 parts focusing on genetic resources and improvement, ecophysiology and production, pests and diseases and their management and harvesting, processing and utilization of sweet and sour cherries.